Insect Diversity and Dominance on Malay Apple (Syzygium malaccense L.) Plantation at Liwa Botanical Garden, West Lampung, Indonesia - Luna Lukvitasari; Ari Saputra; Yuyun Fitriana; Jon Hendra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Malay apple (Syzygium malaccense L.) is a tropical fruit species grown in the fruit garden section of Liwa Botanical Garden, West Lampung, Indonesia. Insect communities play an important role in agroecosystems because they consist of both pest species and beneficial organisms such as predators and parasitoids. This study aimed to determine insect diversity and dominance on Malay apple plantations in the Fruit Garden of the Regional Technical Implementation Unit (UPTD) of Liwa Botanical Garden. The observation was conducted from September to October 2021 using direct observation, pitfall traps, and yellow sticky traps across five sampling plots arranged diagonally. Insect identification was conducted based on morphological characteristics using relevant literature. Species diversity was evaluated using the Shannon–Wiener diversity index (H’), while dominance was measured using Simpson’s dominance index (C). A total of 1,594 insect individuals belonging to nine orders were recorded, including Diptera, Hymenoptera, Orthoptera, Hemiptera, Coleoptera, Lepidoptera, Dermaptera, Odonata, and Neuroptera. The diversity index (H’) was 1.44, indicating moderate diversity, while the dominance index (C) was 0.43, suggesting low dominance. Diptera was the most abundant order, dominated by fruit flies (Bactrocera dorsalis and Bactrocera cucurbitae). The results indicate that the insect community structure in the Malay apple plantation is relatively balanced, although fruit flies have the potential to become major pests. Increasing plant diversity through flowering plants (refugia) is recommended to support beneficial insect populations and maintain ecosystem stability.